Estudo empírico sobre o comportamento do retorno e da liquidez média das ações no mercado acionário brasileiro das empresas que emitiram ADRs na NYSE e das que aderiram ao novo mercado - Neves, Loren Cristina (2008)
The effects in market increase and in average liquidity of the shares, in the two situations: when some companies adept and adopt the requirements of New Market and when some companies emission ADRs, and so meet the requirements of Sarbanes- Oxley are assessed in this research using the methodology Event Study. The events considerate were the dates of adept New Market and the dates of deposit form 20-F in SEC, after the time limit of adjustments for meet the law. The test-t of Student assuming a level of significance the 5% was used for index performance of the abnormal return and the average liquidity, in the period (-15) to (+15) days around the events dates. The results highlight that didn t have statistic differences that allow affirm that Brazilian market increase more value to the companies that issues ADRs in NYSE. And the statistics differences in behavior of the average liquidity of the shares in these companies didn t have. However, they noted statistics differences in the behavior of the average liquidity of the preference shares on the ordinary shares in the companies that issues ADRs in NYSE.